Impact of community-based chronic obstructive pulmonary disease service, a multidisciplinary intervention in an area of high deprivation: a longitudinal matched controlled study. Issue 5 (27th May 2020) - Saini, Pooja; Rose, Tanith; Downing, Jennifer; Matata, Bashir; Pilsworth, Samantha; Pemberton, Allan; Comerford, Terence; Wilson, Keith; Shaw, Matthew; Harper, Lesley M; Daras, Konstantinos; Barr, Benjamin
Abstract : Objective: To examine the effects of a consultant-led, community-based chronic obstructive pulmonary disease (COPD) service, based in a highly deprived area on emergency hospital admissions. Design: A longitudinal matched controlled study using difference-in-differences analysis to compare the change in outcomes in the intervention population to a matched comparison population, 5 years before and after implementation. Setting: A deprived district in the North West of England between 2005 and 2016. Intervention: A community-based, consultant-led COPD service providing diagnostics, treatment and rehabilitation from 2011 to 2016. Main outcome measures: Emergency hospital admissions, length of stay per emergency admission and emergency readmissions for COPD. Results: The intervention was associated with 24 fewer emergency COPD admissions per 100 000 population per year (95% CI −10.6 to 58.8, p=0.17) in the postintervention period, relative to the control group. There were significantly fewer emergency admissions in populations with medium levels of deprivation (64 per 100 000 per year; 95% CI 1.8 to 126.9) and among men (60 per 100 000 per year; 95% CI 12.3 to 107.3). Conclusion: We found limited evidence that the service reduced emergency hospital admissions, after an initial decline the effect was not sustained. The service, however, may have been more effective in some subgroups.